2013
DOI: 10.1038/bjc.2013.672
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125b acts as an oncogene in glioblastoma cells and inhibits cell apoptosis through p53 and p38MAPK-independent pathways

Abstract: Background:We have recently identified miR-125b upregulation in glioblastoma (GMB). The aim of this study is to determine the correlation between miR-125b expression and malignant grades of glioma and the genes targeted by miR-125b.Methods:Real-time PCR was employed to measure the expression level of miR-125b. Cell viability was evaluated by cell growth and colony formation in soft-agar assays. Cell apoptosis was determined by Hoechst 33342 staining and AnnexinV-FITC assay. The Luciferase assay was used to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 36 publications
1
49
0
1
Order By: Relevance
“…In contrast, cell proliferation, clone formation, migration, and invasion were significantly promoted in MKN-45 cells with transfected MiR-125bm; therefore, we explored the tumorpromoting role for MiR-125b in gastric cancer for the first time and possible evidence of the potential usefulness of MiR-125b in MiRNA-based cancer therapy. MiR-125b has various regulating pathways in the process of cell proliferation, differentiation, and apoptosis, such as inhibiting p53-induced apoptosis during development and the stress response [14], inhibiting cell apoptosis through p53 and p38-MAPK-independent pathways in glioblastoma cells [21], targeting EPO and EPOR to correlate with metastatic potential, and expressing ERBB2/HER2 in breast cancer [22]. In this study, to explore the potential targets of MiR125b that might influence proliferation and migration ability of gastric cancer cells, PPP1CA was found among the potential targets of the MiR-125b combination predicted by TargetScan, Pictar-Vert, and Microrna.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cell proliferation, clone formation, migration, and invasion were significantly promoted in MKN-45 cells with transfected MiR-125bm; therefore, we explored the tumorpromoting role for MiR-125b in gastric cancer for the first time and possible evidence of the potential usefulness of MiR-125b in MiRNA-based cancer therapy. MiR-125b has various regulating pathways in the process of cell proliferation, differentiation, and apoptosis, such as inhibiting p53-induced apoptosis during development and the stress response [14], inhibiting cell apoptosis through p53 and p38-MAPK-independent pathways in glioblastoma cells [21], targeting EPO and EPOR to correlate with metastatic potential, and expressing ERBB2/HER2 in breast cancer [22]. In this study, to explore the potential targets of MiR125b that might influence proliferation and migration ability of gastric cancer cells, PPP1CA was found among the potential targets of the MiR-125b combination predicted by TargetScan, Pictar-Vert, and Microrna.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of miR-125b is shown in Table 1. Upregulation of miR-125b as an oncogene has been reported in various cancers: nasopharyngeal carcinoma (NPC), 13,14 retinoblastoma (RB), 15 glioblastoma (GBM), [16][17][18][19][20] poorly differentiated non-small-cell lung cancer (NSCLC), 21 acute lymphoblastic leukemia (ALL), 22 acute myeloid leukemia (AML), 23 and gastric cancer. [24][25][26] On the other hand, miR-125b, as a tumor suppressor, is downregulated in the following cancers: non-small-cell lung cancer (NSCLC), 27 esophageal squamous cell carcinoma (ESCC), 28,29 anaplastic thyroid cancer, 30 bladder cancer, [31][32][33][34][35] hepatocellular carcinoma (HCC), [36][37][38][39] melanoma, 40,41 ovarian cancer, [42][43][44] osteosarcoma, [45][46][47] chondrosarcoma, 48 breast cancer, [49][50][51][52][53][54][55] gallbladder cancer (GBC), 56 endometrioid endometrial cancer (EEC),…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, miR-125b enhanced prostatic xenograft tumors proliferation through downregulation of p53 and Bcl-2-binding component 3 (30). In glioblastoma, Wu et al (26) verified that miR-125b was upregulated and significantly associated with poor prognosis. miR-125b functioned as an oncogene by suppressing cellular apoptosis and enhancing cellular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-125b has been observed to be downregulated in various types of cancer, including oral cancer (23), bladder cancer (18), liver cancer (19), osteosarcoma (20) and endometrial cancer (24). Previous studies have also demonstrated that miR-125b was upregulated in a number of types of cancer, including prostate cancer (25), glioblastoma (26) and pediatric acute promyelocytic leukemia (27). However, there are no studies investigating the expression of miR-125b in LSCC.…”
Section: Discussionmentioning
confidence: 99%